Sindikalne strategije v obdobju krize - Stanojević, Miroslav (Teorija in praksa, 2015)
Trade unions' strategic unadaptability is strongly determined by experiences connected to former (post-war) unions' successful strategies. In conditions marked by a fundamental transition from demand-side to supply-side economics, which was triggered in the early 1980s, unadaptability emerged as a relatively strong factor of the trade unions' decline. Due to this unadaptability, unions are exposed to a spontaneous slide towards 'economistic unionism' and the corresponding long-term trend of membership losses.
Keywords: članstvo; economics; ekonomija; Germany; Italija; Italy; Nemčija; sindikalne strategije; sindikati; Slovenia; Slovenija; Velika Britanija